Organizational Justice Perception of Work Performance and Relationship of Work Performance with the Organizational Opposition Level: A Study on Physical Education and Sports Teachers (Istanbul Province Example - Pekel, Aydın (2021)
The aim of this study is to examine the relationship between the job performance of physical education and sports teachers and their level of organizational justice and opposition. The study group was composed of 575 physical education and teachers of sports who were selected by the simple random method among individuals who worked as physical education and sports teachers in the state schools affiliated to the Istanbul Provincial Directorate of National Education in the 2019-2020 academic year. Data collection methods and tools used in this research; personal information sheet, job performance, organizational justice and organizational opposition scales were implemented. The obtained data were recorded with IBM SPSS 22.0 (version) package program and the all analyzes were accomplished with this statistics program. Descriptive information, subtitles and total scores of the scales were given by determining the frequency (f) and percentage (%) values. Correlation analysis was used as a statistical procedure. As a result, while there was no correlation between physical education and teachers of sport job performance and procedural justice, one of the subtitles of perception of justice, a low level of negative correlation was found between interaction, distributive justice and attitude towards organizational justice total score. Again, no relationship was found between job performance and the total score of vertical and horizontal opposition and organizational opposition which are sub-headings of organizational opposition. This may be due to the fact that administrators do not adequately reward the job performances of physical education and sports teachers due to increasing interest of managers towards teachers who conduct lessons for exams important in terms of students. In addition, it is thought to be caused that physical education and sports teachers do not have any difficulties in expressing themselves due to both their professional competencies and their self-expression and high communication skills that physical education and sports bring them.